PERSEPSI MAHASISWA TENTANG KUALITAS MAKANAN KANTIN FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - FERNANDO, JOAN; Kasmita, Kasmita; Waryono, Waryono (Journal of Home Economics and Tourism, 2014)
The purpose of research is to determine the college student’s perceptions about the food quality cafeteria FT UNP. This research consists of five indicators are: color, appearance, portion temperature and flavor. This type of research is descriptive research using survey method. Population in this research amounted to 8060 people. Sampling technique is non probability sampling, using insidental sampling. Sample number in this research amounted to 100 people. Data collection using a questionnaire based on a Guttman scale that tested for validity and reliability. Based on the results of the study concluded that in general the college students’perceptions about food quality cafeteria FT UNP by 6% of respondents expressed very well, 28% of respondents said good, 59% of respondents said sufficiently, and 7% of respondents said less. If means the college students perception about food quality have score means 7.8 as sufficiently category.Keywords: perceptions, food quality